Control Strategy of Interlinking Converter in Hybrid Microgrid Based on Line Impedance Estimation - Can Wang; Can Deng; Guiyuan Li (Energies, 2022)
Due to the voltage drop of the line impedance, power-transfer deviation occurs in the interlinking converter (IC) of hybrid microgrids. In this paper, an IC control strategy in hybrid microgrids is proposed, which can estimate the line resistance precisely. Moreover, the proposed method can easily realize accurate power transmission between sub-grids and maintain the power balance of hybrid microgrid. Firstly, one specified small signal is injected into the IC at the AC bus of the distributed generation so as to estimate the line impedance. The frequency of the injected small signal is highly relevant to the AC bus voltage. As a result, the IC can accurately detect its line impedance by extracting the injected small signal frequency with a filter and phase-lock-loop (PLL) without communication. Secondly, with the line impedance estimation, the voltage drop on the line can be compensated with local information of the IC, and consequently, accurate power transfer can be realized. Finally, the validity of the proposed method is verified by simulation and experiment results.